Quality by design driven RP-HPLC method optimization for analysis of levothyroxine and liothyronine in bulk and tablet dosage form - Darade, Ramdas; Pekamwar, Sanjay (Creative Pharma Assent, 2025)
Background: Levothyroxine and Liothyronine are widely used in thyroid hormone replacement therapies. Simultaneously quantifying Levothyroxine and Liothyronine is important for managing thyroid hormone deficiency. Aim: This study aims to develop and validate an accurate and robust RP-HPLC method for simultaneously quantifying Levothyroxine and Liothyronine by utilizing Quality by Design (QbD). Methodology: Reversed phase chromatography was performed using a High Performance Liquid Chromatographic System (Agilent Technologies Ltd, 1100 series) equipped with a UV detector. The column used was Agilent C 18 (100 mm x 4.6 mm; 5µm) HPLC Column. The chromatographic separation was carried out using a mobile phase composed of Methanol and Formic acid (0.1%) (50:50 %v/v) with a flow rate of 1.2 ml/min, and a UV detector recorded the response at 254 nm. Design expert was used as software to evaluate experimental design studies (Stat-Ease Inc., Minneapolis, USA, Version 13.0). Result and Discussion: The RP-HPLC method was established to quantify Levothyroxine and Liothyronine simultaneously. The established method was linear, and correlation coefficients (R2) were 0.9993 and 0.9994 for Levothyroxine and Liothyronine, respectively. Retention times of Levothyroxine and Liothyronine were 2.587 minutes and 3.035 minutes. Results of accuracy, precision studies, LOD, and LOQ were found within acceptable limits. Conclusion: A robust RP-HPLC method was developed for the simultaneous quantification of levothyroxine and liothyronine by utilizing a QbD. The QbD technique provided a systematic methodology for identifying and optimizing the critical parameters influencing the method's performance.